PERAN BUDAYA ORGANISASI DALAM MENINGKATKAN KINERJA GURU PADA SLBN 1 KOTA BLITAR - Eko Wibowo; Prim Masrokan Mutohar; Imam Fuadi (As-Sulthan Journal of Education, 2026)
The effectiveness of teacher performance is greatly influenced by the strength of organizational culture within the institution's management system. This study explores the strategy for developing discipline and the importance of organizational culture for teacher motivation and work productivity at SLBN 1 Blitar. Furthermore, various obstacles that limit performance optimization were identified. This study used a descriptive qualitative approach. Data collection techniques included field observations, in-depth interviews, and document reviews. Research subjects included the principal, teachers, and the school committee. The results showed strengthening teacher discipline through a regulatory compliance approach. The implementation of this policy refers to the school's internal standards and the applicable legal framework. The school strives to improve teacher performance through non-binding incentives, job promotions, support for competency development through various training programs. Welfare aspects are also addressed through occupational safety guarantees and the creation of a conducive work environment. Efforts to optimize teacher performance are hampered by minimal regulation dissemination and weak coordination and communication between employees. Another obstacle is the low participation of the school committee, especially in the process of formulating strategic school policies.